Use of GnRH antagonists in ovarian remnant syndrome experimentally induced in rats - Risvanli, A.; Kumru, S.; Akpolat, N.; Yildiz, S. (Imr Press, 2008)
Purpose: The objective of this study was to demonstrate the efficacy of cetrorelix, a GnRH antagonist, in rats with experimentally induced ovarian remnant syndrome. Methods: 25 Wistar female rats at seven to eight weeks of age and weighing 200-250 g were used. The rats were randomly divided into five groups: the first group was used as a control group; the second and third groups underwent a sham operation; and the fourth and fifth groups underwent bilateral hemiovariectomy. At the first proestrus detected by vaginal cytology from postoperative day 2, the animals in groups 1, 2 and 5 received placebo and the animals in groups 3 and 4 received cetrorelix subcutaneously. In the study, the Kruskal-Wallis analysis of variance was used for comparison of the results of vaginal irrigation, histopathological examination, and of blood FSH and LH values, and the Mann Whitney U-test was used for determination of the differences between the groups. Results: It was determined that according to vaginal cytology results, estrus-like cytological changes disappeared in a shorter time and according to histopathology results, the number of follicles were fewer in the ovarian remnant syndrome-induced and cetrorelix-injected group 4 (p < 0.05), but there was no difference between the groups for FSH and LH concentrations. Conclusions: Ovarian remnant syndrome is a complication of bilateral ovariohysterectomy. In cases with this syndrome, certain treatment is possible with re-operation. However, it may not always be possible to perform an operation, or even if operated, it is difficult to determine the place of the residual ovarian tissue. In this study, it was determined that the use of cetrorelix as a GnRH antagonist in rats with ovarian remnant syndrome reduced the duration of estrogenic affect.
Keywords: GnRH antagonist; ovarian remnant syndrome; rat